Observation and modeling of an unusual spatiotemporal pattern in bioacoustic chorusing - D’Spain, Gerald L.; Rovner, Galina L.; Batchelor, Heidi; Rimington, Dennis B. (Frontiers in Remote Sensing, 2024)
This paper describes an unusual underwater biological chorus recorded in the Southern California Bight and presents a numerical modeling approach that replicates aspects of the chorus. During one experiment, the evolution of the directionality of the chorusing region over time is suggestive of “The Wave”, the human waves performed by fans periodically standing and sitting in sports stadia around the world; here, the region of chorusing periodically propagated upcoast over 20 km of coastline at nearly 1.5 km/s. The chorus occurs predominantly at night in spring and summer, mostly in very shallow waters near the coast. It increases the underwater sound field levels within chorusing regions by 20–30 dB in the 50 Hz to 1 kHz frequency band. The chorus is composed of three parts; 1) a “sunset chorus” which is a 20-to-30 min continuous roar around sunset with received spectral levels up to 100 dB re 1 μPa2/Hz, 2) a “sunrise chorus” of lower level than the sunset chorus, and 3) an all-night-long cycling chorus. The cycling portion is made up of 15-to-20 s periods of higher received spectral levels (up to 90 dB re 1 μPa2/Hz within the chorusing region) each followed by a 10-to-20 s lull in which the spectral levels drop by 4–10 dB. This alternating pattern repeats every 30–40 s throughout the night. The numerical modeling approach is based on the physics of excitable media. A cellular automaton is used to model the two-dimensional spatial grid occupied by the calling animals (units), with each unit being either in the “resting”, “excitable”, or “active (calling)" state at each time step. Transition from resting to excitable and from active back to resting occurs automatically after a fixed period of time in the present state, whereas the probability of transitioning from excitable to active is determined not only by the elapsed time since entering the excitable state, but also by the received sound level at the unit location, creating a non-linear acoustics-based coupling between units. With appropriate inputs, many determined from measurements of the chorus properties and the individual animal calls themselves, simulations with the model can replicate the cycling levels in the night-long chorus, the continuous din of the sunset chorus, and (once properly initialized) the periodic upcoast evolution of the chorusing region (“The Wave”). When noise from a transiting ship is included in the simulations, the spatiotemporal characteristics of the chorus change appreciably, in ways similar to changes observed during the experiment.